A hybrid steel–shape memory alloy prestressed concrete beam for improved fire resistance. Issue 10 (5th August 2020) - Jia, Ying‐Qi; Lu, Zhou‐Dao; Li, Ling‐Zhi; Wang, Chao
Summary: Prestressed concrete beams are widely used in structures and infrastructures for their superior control effects on cross‐sectional area, cracking, and deformation. However, the fire resistance of ordinary prestressed beams is unsatisfactory due to the serious material degradation of concrete and steel, as well as the prestress loss at elevated temperatures. To achieve an acceptable fire resistance for prestressed concrete beams, the introduction of shape memory alloy (SMA) is proposed via the hybrid usage of prestressed steel and SMA bars. When the hybrid steel–SMA prestressed beam is exposed to fire, both the strength and modulus of elasticity of prestressed SMA bars will increase, which can compensate for the material degradation of prestressed steel bars. In addition, a desirable recovery stress can be generated in SMA bars at elevated temperatures and further compensate for the prestress loss of prestressed steel bars. To study the fire resistance of the proposed beam, the fitting formulae of material properties of concrete, steel, and SMA at elevated temperatures are given firstly. Then, the analytical model and working mechanism of the hybrid beam are also presented. Further, the methodology for the prediction of fire resistance, and the formulae for the calculation of beam's flexural bearing capacity and deflection, are also presented. A parametric study is further conducted to investigate the relationships between fire resistance and the area and location of prestressed SMA bars. Moreover, an optimal analysis is also established to obtain the most economical material cost of SMA bars. As a result, the proposed prestressed beam can achieve a better fire resistance in terms of both flexural bearing capacity and deflection control.